Degradation of Matured Landfill Leachate by Electro Fenton Treatment and Optimization by Response Surface Methodology - Pieus T, Minimol; P.A, Soloman (International Journal of Engineering and Technology, 2018)
The landfill is the most widely utilized approach for solid waste management over the world. The fluid side-effect of the procedure, leachate, is a genuine danger to the earth. The ordinary biological treatment of matured landfill leachate is restricted by the presence of toxic contaminants and recalcitrant organics. A novel approach for management of landfill leachate by Electro Fenton process is researched here for the technical feasibility. The experimental outcome demonstrated that there was extensive reduction in COD-78.2%, Ammonia nitrogen-42.0%, Chloride-63.5%, Sulfate-60.0%, Sulfide-57.3%, and Phosphate-62.4% at the optimum working state of pH-2.85, Current density-140.5 A/m2, H2O2 dosage- 53% of theoretical value, Reaction time-44min. The biodegradability index was enhanced from 0.21 to 0.43 because of the treatment. The examination not just uncovers the likelihood of degradation of contaminants by giving a mild electrochemical treatment additionally extends the possibility of utilizing the approach as a compelling pretreatment for its biological treatment.Â Â